Ricoeur's Hermeneutics as A Method for Liturgical Theology according to Zimmerman: Hermeneutika Ricoeur sebagai Sebuah Metode bagi Teologi Liturgi menurut Zimmerman - Firmansyah, Antonius (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2025)
This paper investigates the extent to which the application of Ricoeur's hermeneutics according to Joyce Ann Zimmerman can be a method for Liturgical Theology to understand the process of communication of faith during the Liturgy for the Church in the postmodern era. With the need to deepen the interdisciplinary dialogue between liturgy and other branches of science, this paper aims to delineate the point of convergence between Liturgical Theology and hermeneutics to create a more relevant application for Christians today. For this purpose, the methodology used in this paper is a literature study to dialogue Zimmerman’s thoughts with other thinkers focusing on the application of hermeneutics in Liturgical Theology. This paper finds that the application of Ricoeur’s hermeneutics according to Zimmerman can map the linguistic dynamics of liturgical celebrations to enable the transformation of the entire narrative of their life experiences into a narrative of faith. Nevertheless, this method needs to be complemented by the hermeneutics of real dialogical actions with the mystery of God action as a trigger for a deeper transformation of mystical experience in the liturgy towards social ethics. Abstrak Makalah ini mempertanyakan sejauh mana penerapan hermeneutika Ricoeur menurut Joyce Ann Zimmerman bisa menjadi metode bagi Teologi Liturgi untuk memahamai proses komunikasi iman dalam Liturgi di era postmodern. Dengan adanya kebutuhan untuk memperdalam dialog interdisipliner antara liturgi dan cabang-cabang ilmu lainnya, makalah ini bertujuan memperuncing titik temu antara Teologi Liturgi dan hermeneutika demi aplikasi yang lebih relevan bagi umat di masa kini. Metodologi yang digunakan dalam makalah ini adalah studi pustaka dengan mendialogkan pemikiran Zimmerman dengan pemikir-pemikir lainnya yang berfokus pada penerapan hermeneutika di bidang Teologi Liturgi. Ditemukan bahwa penerapan hermeneutika Ricoeur menurut Zimmerman dapat memetakan dinamika linguistik dari perayaan liturgi yang memungkinkan tranformasi seluruh narasi pengalaman hidup mereka menjadi narasi iman. Meski demikian, menurut penulis metode ini perlu dilengkapi dengan hermeneutika tindakan dialogal liturgis konkret dengan misteri ilahi sebagai pemicu transformasi pengalaman mistik dalam liturgi yang lebih mendalam, menuju ke etika sosial. Kata-kata kunci: hermeneutika, dinamika linguistik, partisipasi, distansiasi, apropriasi, pemahaman